Sens et négatio. Le cas du verbe russe páxnut’ (sentir) - Thomières, Irina (Neophilologica, 2017)
This study will deal with the functioning of the Russian verb páxnut’ in negative contexts. On the one hand, I will describe the personal and impersonal uses of the verb listing the semantic nature of its arguments. The importance of the notions of “prototype” and “functional” odor will be highlighted. On the other hand, I will more specifically analyse the verb páxnut’ in negative contexts. The corpus used indicates that in the sequence ne páxnut’ + a substantive in the instrumental, the verb may take on a metaphorical meaning. I will try to determine what factors (semantic nature of the substantive in the instrumental, presence of particles) condition this metaphorical interpretation in which ambiguity is inevitable. The notion of relevance will be used at several levels in this study.